Der streit um die hundert taler: begriff und erkenntnis des wirklichen bei Kant und Hegel - Ferreiro, Héctor Alberto (2016)
Fil: Ferreiro, Héctor Alberto. Pontificia Universidad Católica Argentina; Argentina